Change in Compensatory Skills in Cognitive Therapy for Depression - Barber, Jacques P. (American Psychiatric Press, Inc, 2001)
The Ways of Responding (WOR) was developed to assess change in compensatory or metacognitive skills taught by cognitive therapists. Thus, one would expect WOR scores to change during cognitive therapy (CT) and to be associated with change in depression level. Twenty-seven patients with a DSM-III-R diagnosis of major depression who had received CT filled out the WOR and other measures of cognition. After 12 weeks of CT, the patients exhibited change in the WOR, the Attributional Style Questionnaire, the Dysfunctional Attitude Scale, and the Self-Control Scale. Furthermore, there were indications that change in depression was associated with changes in these measures of cognition, including the WOR. The WOR appears to be a sensitive measure of change during CT that covaries with change in depression. It remains to be tested whether change on the WOR is specific to CT.